2022
DOI: 10.1111/apha.13784
|View full text |Cite
|
Sign up to set email alerts
|

Galectin‐3 enhances atrial remodelling and arrhythmogenesis through CD98 signalling

Abstract: Aim Galectin‐3 (Gal‐3) is a biomarker of atrial fibrillation (AF) that mediates atrial inflammation. CD98 is the membrane surface receptor for Gal‐3. Nevertheless, the role of the Gal‐3/CD98 axis in atrial arrhythmogenesis is unclear. In this study, we investigated the effects of Gal‐3/CD98 signalling on atrial pathogenesis. Methods Whole cell patch clamp and western blotting were used to analyse calcium/potassium homeostasis and calcium‐related signalling in Gal‐3‐administrated HL‐1 atrial cardiomyocytes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…(35). Unexpectedly, we observed that atrial fibrillation was more frequent in profile 1 patients, underlining the newly identified role of both local and systemic inflammation on atrial fibrillation occurrence (45)(46)(47).…”
Section: Discussionsupporting
confidence: 52%
“…(35). Unexpectedly, we observed that atrial fibrillation was more frequent in profile 1 patients, underlining the newly identified role of both local and systemic inflammation on atrial fibrillation occurrence (45)(46)(47).…”
Section: Discussionsupporting
confidence: 52%
“…47 NF-κB can down regulate calcium channels and then cause AF. 48 Atrial heterogeneity is associated with varying degrees of iron infiltration into the myocardium. P-wave dispersion is the difference between the same patient's maximum P-wave duration and the minimum P-wave duration.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Another mechanism is that oxidative stress activates nuclear factors‐κB(NF‐κB) 47 . NF‐κB can down regulate calcium channels and then cause AF 48 …”
Section: Oxidative Stressmentioning
confidence: 99%
“…Gal-3 poses pro-fibrotic effects upon the atrial interstitium, promoting arrhythmogenesis through CD98 (its membrane surface receptor) signaling [ 48 ]. As fibrosis is the main precipitant factor for the development of atrial fibrillation (AF), the biomarker role of Gal-3 in AF has been proposed [ 49 ].…”
Section: Gal-3 and Cardiac Remodelingmentioning
confidence: 99%